Blood‐based biomarkers of human papillomavirus–associated cancers: A systematic review and meta‐analysis. Issue 6 (3rd December 2020) - Balachandra, Sanjana; Kusin, Samuel B.; Lee, Rebecca; Blackwell, James‐Michael; Tiro, Jasmin A.; Cowell, Lindsay G.; Chiang, Cheng‐Ming; Wu, Shwu‐Yuan; Varma, Sanskriti; Rivera, Erika L.; Mayo, Helen G.; Ding, Lianghao; et al.
Abstract : Background: Despite the significant societal burden of human papillomavirus (HPV)–associated cancers, clinical screening interventions for HPV‐associated noncervical cancers are not available. Blood‐based biomarkers may help close this gap in care. Methods: Five databases were searched, 5687 articles were identified, and 3631 unique candidate titles and abstracts were independently reviewed by 2 authors; 702 articles underwent a full‐text review. Eligibility criteria included the assessment of a blood‐based biomarker within a cohort or case‐control study. Results: One hundred thirty‐seven studies were included. Among all biomarkers assessed, HPV‐16 E seropositivity and circulating HPV DNA were most significantly correlated with HPV‐associated cancers in comparison with cancer‐free controls. In most scenarios, HPV‐16 E6 seropositivity varied nonsignificantly according to tumor type, specimen collection timing, and anatomic site (crude odds ratio [cOR] for p16+ or HPV+ oropharyngeal cancer [OPC], 133.10; 95% confidence interval [CI], 59.40‐298.21; cOR for HPV‐unspecified OPC, 25.41; 95% CI, 8.71‐74.06; cOR for prediagnostic HPV‐unspecified OPC, 59.00; 95% CI, 15.39‐226.25; cOR for HPV‐unspecified cervical cancer, 12.05; 95% CI, 3.23‐44.97; cOR for HPV‐unspecified anal cancer, 73.60; 95% CI, 19.68‐275.33; cOR for HPV‐unspecified penile cancer, 16.25; 95% CI, 2.83‐93.48). Circulating HPV‐16 DNA was a valid biomarker for cervical cancer (cOR, 15.72; 95% CI, 3.41‐72.57). In 3 cervical cancer case‐control studies, cases exhibited unique microRNA expression profiles in comparison with controls. Other assessed biomarker candidates were not valid. Conclusions: HPV‐16 E6 antibodies and circulating HPV‐16 DNA are the most robustly analyzed and most promising blood‐based biomarkers for HPV‐associated cancers to date. Comparative validity analyses are warranted. Variations in tumor type–specific, high‐risk HPV DNA prevalence according to anatomic site and world region highlight the need for biomarkers targeting more high‐risk HPV types. Further investigation of blood‐based microRNA expression profiling appears indicated. Abstract : A number of blood‐based biomarkers for HPV‐associated cancers have been evaluated. Among these, HPV‐16 E6 antibodies and circulating HPV DNA have exhibited the most promising performance characteristics.